Investigation of Oxygen Transport Resistance in M-ACLS Electrodes for PEFC Cathodes. (24th August 2017) - Kanai, Yuta; Fukazawa, Taishi; Yoshida, Takashi; Nakano, Yoshihiko; Mei, Wu
Abstract : Modified alternating catalyst layer structure (M-ACLS) is a promising low-platinum technology for application in polymer electrolyte fuel cells (PEFCs). Because the catalyst layer structure of an M-ACLS electrode is characterized by nanosheet platinum, which differs from the commonly used Pt/C, it is necessary to understand the oxygen transport capability. In this study, the oxygen transport resistance was investigated using limiting current measurement. It is found that, compared with Pt/C, M-ACLS cathodes exhibited far lower oxygen transport resistance per unit platinum surface area.